The Comparison of the Executive-Neurological Functions of the Narcotic Addicted and Normal Adults - Fereshteh Amini; Hamid Alizadeh; Omid Rezaee (Drug Control Headquarters, Research and Education Office, 2010)
Aim: The purpose of present research was the comparison of executive-neurological functions of narcotics addicted and normal adults. Method: In this causal-comparative study 38 narcotics addicted person selected of two addiction treatment clinics in Tehran, and 38 normal persons selected through available sampling. The both groups assessed by neuropsychological tests namely: the Wisconsin classification cards. Results: The analysis of data indicated the significant difference on executive functions of addicted and normal groups. That is addicted group were poorer than normal group on executive functions. Conclusion: The findings of present research showed the addicts have weaker executive functions than the normal persons. In other words, the addicts showed impairments on cognitive flexibility and formation of change concepts.